Crystal structure and morphology of CeO2 doped stabilized zirconia ceramics under high-frequency microwave field sintering. Issue 8 (15th April 2022) - Ling, Yeqing; Hao, Xiandong; Zhang, Sirui; Chen, Jin; Gao, Lei; Omran, Mamdouh; Chen, Guo
Abstract: Under high-frequency microwave irradiation, zirconia ceramics were prepared by sintering nano-CeO2 (Ce = 7 mol%) doped zirconia powder. The different effects of temperature environment on the phase structure transformation, surface functional groups, microstructure, growth process, and density of doped zirconia were analyzed, and the optimized microwave sintering process for zirconia was determined. The experimental results reveal that the tetragonal phase of zirconia is positively correlated with the temperature when the temperature reaches about 1100 °C in the studied range. The reason is that the grain grows with the increase of sintering temperature, and the surface energy of grain decreases, which leads to the fluctuation of tetragonal phase content. The density of zirconia reaches 98.03% at 1300 °C, and the growth activation energy is 27.40 kJ/mol. There is no abnormal growth of zirconia particles, and the phase transition temperature decreases, which is attributed to the efficient heating of microwave and the incorporation of nano-ceria stabilizer.